Pengaruh Jenis Gula terhadap Karakteristik Kimia dan Organoleptik Kue Sagon Ampas Kelapa: Effect of Different Sugar Types on the Chemical and Organoleptic Characteristics of Coconut Pulp Sagon Cake - Mujibu Rahman; Natalia Marlinang Sihombing; Farida Aryani; Hamka; Andi Lisnawati; Jamaluddin; Zainal Abidin (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2026)
Sagon cake is a traditional Indonesian food that can be further developed through the utilization of coconut pulp as a value-added raw material. This study aimed to analyze the effect of different sugar types on the chemical and organoleptic characteristics of coconut pulp sagon cake. A Completely Randomized Design (CRD) with one factor and three treatments was applied, namely palm sugar (P1), corn sugar (P2), and coconut sugar (P3), with three replications each. The observed parameters included moisture content, ash content, and organoleptic properties (color, aroma, texture, and taste). Data were analyzed using Analysis of Variance (ANOVA) followed by the Least Significant Difference (LSD) test at the 5% significance level. The results showed that sugar type had a highly significant effect on moisture content (p<0.01) and a significant effect on ash content, color, aroma, and taste (p<0.05), while no significant effect was observed on texture (p>0.05). Coconut sugar treatment produced the lowest moisture content (2.53%) and the highest ash content (1.20%). In the organoleptic evaluation, palm sugar obtained the highest preference scores for color (4.00), aroma (4.28), and taste (4.00), whereas coconut sugar achieved the highest score for texture (3.57). All treatments complied with the quality requirements of SNI 01-4475-1998 for moisture and ash content. The results indicate that coconut sugar has the potential to improve product storage stability due to its lower moisture content compared with the other treatments.